Shalat Dalam Perspektif Al-Qur’an: Kajian Maudhū‘Ī Terhadap Qs. Al-Baqarah, Al-Ḥajj, Dan Al-Isrā’judul - Muhammad Sahrul (Jurnal Kajian Islam dan Sosial Keagamaan, 2025)
The purpose of this study is to examine the meaning of prayer from the perspective of the Qur'an through a thematic approach (tafsīr maudhū‘ī) which focuses on three main verses, namely QS al-Baqarah (2): 43–46, QS al-Ḥajj (22): 77, and QS al-Isrā’ (17): 78. Two classical tafsir books, Tafsīr al-Ṭabarī and Fatḥ al-Qadīr, are used as the main sources to reveal how the Qur'an presents prayer as the foundation of spiritual awareness, moral formation, and social order. This study uses a qualitative-descriptive method based on literature studies, the results of this study found that prayer is not only a ritual obligation, but also a process of inner purification that fosters sincerity, discipline, and concern for others. In the view of the Qur'an, prayer is a spiritual bridge that connects humans with God, fosters calm amidst the dynamics of life, and is a symbol of harmony between the dimensions of ubudiyah and humanity.